Effects of canagliflozin on cardiovascular disease risk factors in patients with type 2 diabetes: a systematic review and meta-analysis - Hossein Aftabi; Reyhaneh Aftabi (BMC Endocrine Disorders)
Abstract Background Canagliflozin or sodium-glucose co-transporter 2 inhibitor (SGLT2i) is considered as an authorized therapeutic drug for treatment of patients with type 2 diabetes mellitus (T2DM). This study reviews and evaluates the effects of Canagliflozin on Hemoglobin (HbA1c), Body Mass Index (BMI) and Systolic Blood Pressure (SBP). Methods This fixed-effects systematic review and meta-analysis are based on 38 comprehensive literature survey and statistical analysis of selected references that explore the effect of canagliflozin in patients having cardiovascular disease (CVD) and T2DM. The data were analyzed and interpreted at 95% Confidence Interval with reference to placebo-controlled randomized controlled trails (RCTs). Results The effects of canagliflozin at 100 and 300 doses slightly reduced Hemoglobin A1c (HbA1c) and Body Mass Index (BMI) without significant differences with placebo [HbA1c at 100 mg, effect size: -0.005, Confidence Interval of 95% = -0.04 to 0.03, (P = 0.79), at 300 mg, effect size: -0.03 (-0.11 to 0.05), (P = 0.43), BMI at 100 mg, effect size: -0.01 (-0.04 to 0.02), (P = 0.57) and at 300 mg, effect size was 0.02 (-0.05 to 0.10), (P = 0.55)]. At 100 mg dose, canagliflozin lowers systolic blood pressure compared to that of placebo (effect size: -0.03 (-0.07, 0.00), (P = 0.06)]. These data up to date reveal that the most significant effective role of canagliflozin in patients having T2DM is to reduce the systolic blood pressure. Conclusion This systematic review and meta-analysis highlight that although canagliflozin does not project significant decrease on BMI and HbA1c, yet in 100 mg doses significantly reduces SBP in patients with T2DM. Further future research in the coming years may provide more data and information on the protective role of canagliflozin in patients with T2DM.